Comment on "Relativistic atomic data for W XLVII" by S. Aggarwal et al. [Chin. Phys. B 24 (2015) 053201]. (9th October 2015) - Aggarwal, Kanti M.
Abstract: Recently, S. Aggarwal et al. [ Chin. Phys. B 24 (2015) 053201] reported energy levels, radiative rates, and lifetimes for the lowest 148 levels belonging to the 3s 2 3p, 3s3p 2, 3s 2 3d, 3s3p3d, 3p 3, 3p 2 3d, 3s3d 2, 3p3d 2, and 3d 3 configurations of Al-like tungsten. While their calculated energies for the levels and the radiative rates for transitions are correct, the reported results for lifetimes are completely wrong. According to our calculations, errors in their reported lifetimes are up to 14 orders of magnitude for over 90% of the levels. Here we report the correct lifetimes and explain the reasons for discrepancies.